PENERAPAN MODEL KOOPERATIF TIPE NHT UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS V SD - Hasanah, Uswatun (JURIDIKDAS, 2024)
This study aims to increase the activity and learning outcomes of grade V students at SDN 07 Bengkulu City by applying the Numbered Head Together cooperative learning model. This type of research is classroom action research. The subjects of this study were teachers and students with a total of 28. The research instruments were observation sheets and test questions. Observation data analysis techniques use the average score formula, the highest score, the lowest score, the difference between the scores and the range of values ​​for each criterion. The test data uses the formula for the average value and percentage of learning completeness. The results showed an increase from cycle I to cycle II, this was obtained from the results of the average teacher activity score of 31.5 increasing to 43.5 while the results of student activity scores obtained an average of 31.5 increasing to 43.5. The results of the evaluation test on Indonesian language content obtained an average score of 71.42 with classical completeness of 64.28%, increasing to 81 and classical completeness of 85.71%. Science content obtained an average score of 72.85 with classical completeness of 64.28%, increasing to 80 and classical completeness of 85.71%. Thus it can be concluded that the application of the Numbered Head Together model can increase activity and learning outcomes in thematic learning for class V SDN 07 Bengkulu City.